2020
DOI: 10.1101/2020.11.24.396242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of cortical control over the descending pain modulatory system determines the development of the neuropathic pain state in rats

Abstract: The loss of descending inhibitory control is thought critical to the development of chronic pain but what causes this loss in function is not well understood. We have investigated the dynamic contribution of prelimbic cortical neuronal projections to the periaqueductal grey (PrL-P) to the development of neuropathic pain in rats using combined opto- and chemo-genetic approaches. We found PrL-P neurons to exert a tonic inhibitory control on thermal withdrawal thresholds in uninjured animals. Following nerve inju… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
(122 reference statements)
1
5
0
Order By: Relevance
“…This is similar to the previous finding from studies of placebo analgesia where naltrexone was shown to disrupt ACC-PAG communication which was also linked to the mediation of its analgesic effects (Eippert et al, 2009a). Activation of an analogous ACC-PAG pathway in rats has recently been shown to produce an analgesic effect mediated via an inhibition of activity at a spinal level indicating that it indeed represents a component of the descending analgesic system (Drake et al, 2021). Interestingly this study also found that this system failed in a chronic neuropathic pain model.…”
Section: Impact Of Neuromodulators On Regional Brain Activations and Network Interactionssupporting
confidence: 89%
“…This is similar to the previous finding from studies of placebo analgesia where naltrexone was shown to disrupt ACC-PAG communication which was also linked to the mediation of its analgesic effects (Eippert et al, 2009a). Activation of an analogous ACC-PAG pathway in rats has recently been shown to produce an analgesic effect mediated via an inhibition of activity at a spinal level indicating that it indeed represents a component of the descending analgesic system (Drake et al, 2021). Interestingly this study also found that this system failed in a chronic neuropathic pain model.…”
Section: Impact Of Neuromodulators On Regional Brain Activations and Network Interactionssupporting
confidence: 89%
“…Furthermore, such an effect is associated with reduced excitability of excitatory neurons in PrL, including the PAG-projecting neurons. These results provide a possible explanation for the impaired PrL-PAG connectivity detected in humans with chronic pain and animal models of chronic pain 32,33 . Our study establishes a new Bdnfdependent mechanism of central sensitization.…”
Section: Discussionmentioning
confidence: 67%
“…2). Such modulation enhances the PrL-vlPAG connectivity, which has been reported to be signi cantly suppressed in neuropathic pain 32 , leading to pain alleviation. Our study provides a molecular and neural circuit perspective for understanding the analgesic-like effects of R-HNK.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, animal studies highlight the impact of decreased anti‐nociceptive mechanisms (Carlton et al, 2009), i.e. spinal disinhibition (Gwak et al, 2006; Zeilhofer, 2008) and loss of descending inhibition (Drake et al, 2021). In human research, the latter has been associated with the spatial extent of SCI‐NP (Gruener et al, 2016).…”
Section: Discussionmentioning
confidence: 99%